Landslide Hazard Zonation in and around Litan Village along NH-202, Ukhrul District, Manipur, India - Okendro, M.; Kushwaha, R. A. S. (National Geographical Journal of India, 2022)
Hazard is multifaceted in nature which includes landslide that pose great threat to lives of people and properties especially in rugged hilly terrains like tectonically active Indo-Myanmar Range. Various ways of landslide susceptibility study have been taken up throughout the globe in order to minimize and mitigate the hazard. Systematic and scientific investigation is the only means to predict the vulnerability of landslides. Landslide Hazard Zonation can property demarcate the hazard prone slopes. The outcome of the present investigation reveals that more than 60% of the total study area falls under highly landslide prone areas